患者側からみた歯科訪問診療の評価 (第1報) - Murata Toshihiro; 瀧 成和; 荒尾 良治; 長妻 満; 中村 新太郎; 山本 雅也; 陸野 隆弘; 綿谷 和也; 神田 矩夫; 臼本 鏡子; 小田 見也子 (Ronen Shika Igaku, 2010)
As the population rapidly ages, there has been an increasing demand for home-visit dental services. We conducted a questionnaire to examine how home-visit dental services help patients achieve self-reliance and reduce the burden on family caregivers.The subjects were 181 patients who received home-visit dental services between April 1999 and March 2005 and their family members. The question items included : 1) changes in the burden of nursing care in daily life (five items) ; 2) changes in oral function (three items) ; 3) evaluation of the services (three items).The majority of the subjects were patients with cerebrovascular diseases, bone fracture, rheumatism, neurological diseases, or muscular disorders, and their chief complaints included: denture problems, eating disorders and dysphagia, decay, and periodontal problems.We collected 66 responses (36.5%). The results of the questionnaire were as follows : 1) approximately 40% felt that the service helped reduce the burden of nursing care ; 2) about 40% recognized an improvement in their oral function ; 3) about 80% hoped that the services would be available on a regular basis. Most of the patients and their families were satisfied with home-visit dental services. Further research should be conducted to examine changes in their awareness of dental health after receiving home-visit dental services. 急激な高齢化の進行にともない, 歯科訪問診療の需要も増加している。今回, 患者からの意見として, 歯科訪問診療が自立支援や介護軽減にどのように寄与しているかを調査するため, 受診者および家族に対してアンケートを実施した。平成11年4月から平成17年3月までに歯科訪問診療を受けた患者および家族 (181件うち65歳以上151件) に対して, (1)日常生活における介護負担の変化 (5項目), (2)口腔機能の変化 (3項目), (3)歯科訪問診療への評価 (3項目) について, 選択·記入式のアンケートを実施した。対象者の多くは, 脳血管疾患, 骨折·リウマチ, 神経筋疾患であり, 依頼内容は義歯調整, 摂食機能療法, う蝕·歯周病処置に関することであった。アンケートの回収は, 66名 (36.5%) であった。アンケート結果より, (1)介護負担の変化について「軽減した」が約40%, (2)口腔機能の変化について「改善した」が約40%, (3)歯科訪問診療の継続について「希望する」が約80%であった。多くの患者および家族が歯科訪問診療を受けて満足していると推察された。今後, 歯科訪問診療を受診した後の歯科保健に対する意識変化についても調査の必要性が考えられた。